2005
DOI: 10.1111/j.1467-7687.2005.00454.x
|View full text |Cite
|
Sign up to set email alerts
|

A shift from diffuse to focal cortical activity with development

Abstract: Recent imaging studies have suggested that developmental changes may parallel aspects of adult learning in cortical activation becoming less diffuse and more focal over time. However, while adult learning studies examine changes within subjects, developmental findings have been based on cross-sectional samples and even comparisons across studies. Here, we used functional MRI in children to test directly for shifts in cortical activity during performance of a cognitive control task, in a combined longitudinal a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

46
418
3
2

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 568 publications
(477 citation statements)
references
References 51 publications
46
418
3
2
Order By: Relevance
“…For example, MeanTS did not have significant associations with age in fronto‐frontal connections, whereas ALPACA's positive associations with age were exclusively found in fronto‐frontal, fronto‐temporal, and fronto‐parietal connections. This is in line with findings of an earlier study that suggested that cortical connections become increasingly focal with age (Durston et al., 2006). This is in contrast with age associations with the posterior cingulate, which were positive in MeanTS but not ALPACA.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, MeanTS did not have significant associations with age in fronto‐frontal connections, whereas ALPACA's positive associations with age were exclusively found in fronto‐frontal, fronto‐temporal, and fronto‐parietal connections. This is in line with findings of an earlier study that suggested that cortical connections become increasingly focal with age (Durston et al., 2006). This is in contrast with age associations with the posterior cingulate, which were positive in MeanTS but not ALPACA.…”
Section: Discussionmentioning
confidence: 99%
“…First, we used the correlation of the mean time series for brain regions involved in a given connection to express uniform and homogenous connectivity. However, connectivity in some regions becomes increasingly focal during development (Durston et al., 2006), which we captured with a new measure of connectivity that determines the focal maxima of correlations between ROIs. Each approach measures different aspects of connectivity, which can help parse whether connectivity differences in development involve larger brain regions or tend to be more focal within an ROI.…”
Section: Introductionmentioning
confidence: 99%
“…Using source localization methods, Jonkman and colleagues found that the neural activity underlying response inhibition in adults was adequately explained by frontal sources, but in children, contributions from additional posterior sources were required. Supporting evidence also comes from studies utilizing brain imaging techniques that have shown that as children develop, the neural networks controlling inhibitory processes shift from a more posterior, distributed pattern to a more frontal, localized one (Bunge et al, 2002; Casey, Thomas, Davidson, Kunz, & Franzen, 2002; Durston et al, 2006). …”
Section: Discussionmentioning
confidence: 99%
“…First, studies point to a gradual development of cognitive control mechanisms over the course of adolescence and early adulthood, consistent with the anatomical changes in the dorsolateral prefrontal cortex described earlier. Imaging studies examining performance on tasks requiring cognitive control (e.g., Stroop, flanker tasks, Go-No/Go, antisaccade) have shown that adolescents tend to recruit the network less efficiently than do adults, and that regions whose activity correlates with task performance (i.e., cognitive control areas) become more focally activated with age (Durston et al, 2006). It has been suggested that this increasingly focal engagement of cognitive control areas reflects a strengthening of connections within the control network, and of its projections to other regions (a claim consistent with data on increased connectivity among cortical areas with development; Liston et al, 2006).…”
Section: Functional Changes In the Cognitive Control Systemmentioning
confidence: 99%